The impact of inclusionary housing on property prices in Cape Town - Roode, Lauren (School of Economics, 2025)
Modern-day South Africa faces a considerable shortfall of urban housing. It also inherited a racially based system of spatial planning from the apartheid state. As a result, poor (and typically black) households reside in peripheral areas of major cities. This spatial structure denies these households easy access to the economic opportunities available in the larger city centers. It has been suggested that both problems could be addressed using a policy of ‘inclusionary housing'. This thesis investigates inclusionary housing's potential in Cape Town, as a means to address both the housing crisis and spatial segregation. Cape Town has a few neighbourhoods, such as Woodstock, that have been de facto inclusionary areas. These areas historically housed families from all walks of life, cultures, races, and income levels. Looking at Woodstock as a “historically inclusive neighbourhood”, this thesis deepens the analysis of the costs and benefits of inclusionary housing by discussing the economic, political, and social trends in this suburb over time. Findings indicate that while inclusionary housing in Cape Town is unlikely to solve the city's housing shortfall, it could contribute to more effective social cohesion and economic inclusion in well located areas. These positive spin offs are achievable through strong regulation of the housing market and consistent support for inclusionary principles from local government, property developers and households.